The effects of organizational communication, leadership, and employee commitment in organizational change in the hospitality sector - Manuel-Alberto Ramos-Maçães; Mercedes Román-Portas (Communication & Society (Formerly Comunicación y Sociedad), 2022)
The purpose of this study was to empirically analyze the interrelationships among organizational communication, leadership, and employee commitment, in terms of organizational change. A structural model was developed to delineate the interactions between the constructs, and to explore the mediating effects of leadership and employees’ commitment on the relationship between communication and organizational change. A quantitative online survey was conducted, based on a sample of 335 employees from the hospitality sector. Findings indicated that organizational communication positively and significantly affected leadership and employee commitment and was positively related to organizational change. Furthermore, this study argues that communication, leadership, and employee commitment are key variables in the success of organizational change. The findings can provide academics and managers with a valuable and much-needed approach to managing change, by identifying the predictors of organizational change, and by exploring how individual antecedents affect the success of organizational change.